A new transgenic mouse model for conditional overexpression of the Polycomb Group protein EZH2 - Koppens, Martijn A. J.; Tanger, Ellen; Nacerddine, Karim; Westerman, Bart; Song, Ji-Ying; van Lohuizen, Maarten (Transgenic research, 2017)
The Polycomb Group protein EZH2 is upregulated in most prostate cancers, and its overexpression is associated with poor prognosis. Most insights into the functional role of EZH2 in prostate cancer have been gained using cell lines and EZH2 inactivation studies. However, the question remains whether overexpression of EZH2 can initiate prostate tumourigenesis or drive tumour progression. Appropriate transgenic mouse models that are required to answer such questions are lacking. We developed one such transgenic mouse model for conditional overexpression of Ezh2 . In this transgene, Ezh2 and Luciferase are transcribed from a single open reading frame. The latter gene enables intravital bioluminescent imaging of tissues expressing this transgene, allowing the detection of tumour outgrowth and potential metastatic progression over time. Prostate-specific Ezh2 overexpression by crossbreeding with Probasin - Cre mice led to neoplastic prostate lesions at low incidence and with a long latency. Compounding a previously described Bmi1 -transgene and Pten -deficiency prostate cancer mouse model with the Ezh2 transgene did not enhance tumour progression or drive metastasis formation. In conclusion, we here report the generation of a wildtype Ezh2 overexpression mouse model that allows for intravital surveillance of tissues with activated transgene. This model will be an invaluable tool for further unravelling the role of EZH2 in cancer.